Red Hibiscus - Asis, Zea (Likhaan: The Journal of Contemporary Philippine Literature; Vol 16 No 01 (2022): LIKHAAN 16: The Journal of Contemporary Philippine Literature, 2023)
“Red Hibiscus” recounts a young girl’s childhood in Butuan City, revealing her sensory and carnal experiences to create a memoir of the body, of her own despair and rage growing up in a household of complex familial love and domestic violence. It charts the narrator’s many griefs, starting from her loss of innocence as a child to her father’s untimely death many years later, to show the ways that we come to terms with our own personal tragedies in order to live again.